1997
DOI: 10.1021/la970933h
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Protein Molecules onto Homogeneous and Mixed Carboxylate-Terminated Self-Assembled Monolayers

Abstract: The attachment of biomolecules, in particular proteins, onto solid supports is fundamental in the development of advanced biosensors, bioreactors, affinity chromatographic separation materials, and many diagnostic techniques. In addition, the effective investigation of biomolecular structure and function with scanning probe microscopy often requires a strong attachment of the biomolecule to a substrate. Here, we investigate the binding of the protein catalase to gold surfaces modified by self-assembled monolay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
255
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(268 citation statements)
references
References 29 publications
10
255
0
1
Order By: Relevance
“…36 Hence, although the net charge of a protein is negative, positively charged patches on the protein surface are also present due to the heterogeneous distribution on the protein surface. 37,38 Park et al demonstrated positive charge patches in bovine serum albumin (BSA) (that is otherwise negatively charged), 39 allowing BSA to bind with a strong polyanion, as also observed in this work and in a previous report. 32,38 The protein could also carry multiple positive charges and therefore be able to replace the counterions on a polymer surface.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
“…36 Hence, although the net charge of a protein is negative, positively charged patches on the protein surface are also present due to the heterogeneous distribution on the protein surface. 37,38 Park et al demonstrated positive charge patches in bovine serum albumin (BSA) (that is otherwise negatively charged), 39 allowing BSA to bind with a strong polyanion, as also observed in this work and in a previous report. 32,38 The protein could also carry multiple positive charges and therefore be able to replace the counterions on a polymer surface.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
“…Indeed, mixed SAMs containing long and short alkanethiols have proven most effective for protein immobilization. 47 A short adsorption time can also help minimize multilayer formation onto the gold surface. 56 SPR images of the grating arrays were acquired by collecting the reflected light intensity (R p /R s ) over the sample surface at a fixed angle of incidence and a single wavelength with the grating orientation perpendicular to the light path.…”
Section: Resultsmentioning
confidence: 99%
“…58,59,225 We reason this as the major cause behind the limited number of literature examples on this directive approach, while on the other hand the step-wise NHS/EDC activation scheme (Si-RCOOH to Si-RC(O)NHS) remain widespread in surface science. 50,51,226,227 It is also worth noting that an optimization study to evaluate the optimal range of NHS and EDC concentrations and molar ratios has only very recently been published for porous silicon substrates by Sam et. al.…”
Section: Formation and Derivatization Of Carboxylic Acid-based Monolamentioning
confidence: 99%